Versatile Enzymatic Approach for Truncation, Labeling, and Mutation of Nucleobase-Modified Aptamers Demonstrated on Indole-Modified β-Conglutin Aptamer - Ondruš, Marek; Franco-Urquijo, Pablo Alberto; Lerga, Teresa Mairal; Mužíkova Čechová, Lucie; Bermudo Redondo, M Carmen; O Sullivan, Ciara K; Hocek, Michal (Chembiochem, 2025)
A new enzymatic method for truncation of aptamers from 5'-end has been developed and demonstrated on a newly selected indole-modified β-conglutin aptamer. This method relies on extension of a primer containing ribonucleotides, which can be specifically hydrolyzed by RNase, thereby removing the whole or 5'-part of the primer. This approach enables flexible synthesis of modified aptamers truncated from the 5' end, 3' end, or both ends-a capability previously achievable only through chemical oligonucleotide synthesis. Furthermore, by employing doubly labeled primers, diverse labeled or modified nucleotides are introduced to prepare 5'-labeled aptamers suitable for fluorescence- or immobilization-based assays. The different variations of this method also enable the synthesis of mutated sequences to study the effect of modifications and their positions. Overall, this enzymatic method provides a valuable alternative for the truncation or labeling of (hyper)modified and functional oligonucleotides avoiding the need for chemical synthesis.
Keywords: polymerases; aptamers; oligonucleotides; Aptamers, Nucleotide; Indoles; nucleotides; mutace; aptamery nukleotidové; ribonukleasy; indoly; Mutation; Ribonucleases; enzymatic syntheses